Caracterização dielétrica, estrutural e magnética em soluções sólidas 0,9bifeo3-0,1batio3 dopadas com manganês - Alonso, Raquel de Santana (2020)
The present work aims to carry out the dielectric, structural and magnetic characterizations of materials 0,9BiFeO3-0,1BaTiO3 system, doped with manganese. In a first stage, the samples were processed by high energy mill and sintered by the conventional process. Manganese additions were made in certain amounts for subsequent analysis and comparisons of the samples. This study aims to present and discuss the results of X-ray diffraction measurements (DRX), magnetic hysteresis and also dielectric analysis of the material. The results of diffraction can be identified through the major phase like a rhombohedral structure of the R3c space group. A significant magnetization increase (0,50 emu/g) was observed for Mn - doped samples. Dielectric results demonstrate a probable performance of manganese improving dielectric properties in low doping percentages. The dielectric characterization also revealed that for the undoped sample, two conductivity mechanisms are present, one starting around 177 K and the other around 325 K. In the doped samples, one of these mechanisms was suppressed, increasing the resistivity and decreasing the dielectric losses of the samples.